2013
DOI: 10.1007/s00105-013-2587-0
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapie und Karzinogenese

Abstract: Phototherapie ist, wie in den anderen DNS-Schäden bei PhototherapieVerschiedene Wellenlängen kommen bei der Phototherapie zum Einsatz. Am besten beschrieben sind Effekte für PUVA und UVB in ihrer Wirkung auf die DNS.UVB und "UVB narrow band" (UVBnb; synonym mit UVB-Schmalband, UVB 311 nm) unterscheiden sich um das 10-Fache in der therapeutisch angewandten Energiedosis. Klinische Karzinogenese nach PhototherapiePsoriatiker mit PUVA-Behandlung stellen die bestdokumentierte Patientengruppe mit langfristiger Nach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
12
0
2
Order By: Relevance
“…None of the studies except the studies of Jekler and Lark€ o 21,26 (which were not performed during summer months) mentioned the possibility of seasonal effects on the remission of AD. 39 Nevertheless, according to recent guidelines, the use of photo(chemo)therapy in children, who are most commonly affected in AD, should be avoided. Moreover, only a few studies reported the used emission spectra, while standard spectra often exceed the official wavelengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the studies except the studies of Jekler and Lark€ o 21,26 (which were not performed during summer months) mentioned the possibility of seasonal effects on the remission of AD. 39 Nevertheless, according to recent guidelines, the use of photo(chemo)therapy in children, who are most commonly affected in AD, should be avoided. Moreover, only a few studies reported the used emission spectra, while standard spectra often exceed the official wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…38 According to a recent published review, BB-UVB, NB-UVB and UVA1 have not yet been directly linked to cutaneous carcinogenesis, but long-term follow-up studies are needed. 39 Nevertheless, according to recent guidelines, the use of photo(chemo)therapy in children, who are most commonly affected in AD, should be avoided. 4 In our opinion, high-level evidence with long-term follow-up should be obtained for children with AD to explore whether phototherapy may be a treatment option in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The solar UV spectrum can be divided into UVA (315–400 nm), UVB (280–315 nm), and UVC (100–280 nm) radiation [1,2]. Short-wavelength UVC (especially 254 nm) and medium-wavelength UVB readily produce DNA photoproducts such as cyclobutane pyrimidine dimers (CPD) and pyrimidine-pyrimidone (6-4) photoproducts (6-4PP) [3,4]. Because these photolesions interfere with DNA replication and transcription, they can lead to cell death and mutagenesis, thereby threatening genome stability [5].…”
Section: Introductionmentioning
confidence: 99%
“…But additional factors as previous UV damage due to chronic sun exposure and sun burns, immunosuppressive treatment, increase cutaneous carcinogenesis through PUVA. In contrast, other artificial UV treatment as broadband UVB, narrowband UVB, and UVA1 has not yet been linked to cutaneous carcinogenesis probably due to lack of large follow-up studies [21] . One retrospective study including 92 patients affected by psoriasis under treatment with narrowband UVB or PUVA-therapy showed noteworthy number of non-melanoma skin cancer [22] .…”
Section: Discussionmentioning
confidence: 99%